A High Precision Laser-Based Autofocus Method Using Biased Image Plane for Microscopy. (10th May 2018) - Gu, Chao-Chen; Cheng, Hao; Wu, Kai-Jie; Zhang, Liang-Jun; Guan, Xin-Ping
Abstract : This study designs and accomplishes a high precision and robust laser-based autofocusing system, in which a biased image plane is applied. In accordance to the designed optics, a cluster-based circle fitting algorithm is proposed to calculate the radius of the detecting spot from the reflected laser beam as an essential factor to obtain the defocus value. The experiment conduct on the experiment device achieved novel performance of high precision and robustness. Furthermore, the low demand of assembly accuracy makes the proposed method a low-cost and realizable solution for autofocusing technique.